Does environmental regulation affect urban green technology innovation in China? Evidence from the low-carbon city pilot policy - Li, Zhuo; Liu, Zhe (Frontiers in Energy Research, 2023)
The Low-carbon City Pilot (LCCP) policy is a new environmental governance model to achieve carbon neutrality, promote low-carbon pilot city development, and address climate change. Taking LCCP policy as an exogenous shock, this paper examines the impact of LCCP policy on urban green technology innovation and its transmission mechanism from 2005 to 2017. Based on the Difference- in-Difference (DID) method, the following results are obtained: The LCCP policy can promote urban green technology innovation, and the results remain robust through a series of robustness tests. Mechanism analysis shows that LCCP improves the level of green technology innovation in two ways, it encourages local governments to increase R&D funds and forces pollution-intensive and energy-consuming industries to upgrade industrial structures. In addition, the conclusion also reveals that the urban location characteristics and the intensity of environmental regulation have a heterogeneous impact on green technology innovation, with the most significant effect on the western region. Therefore, policymakers must mobilize the autonomy of local governments, increase the investment of local government R&D funds, and strive to spread the pilot policy of low-carbon cities to the whole country to promote industrial transformation.